Desain Didaktis dengan Pembelajaran Matematika Realistik Pada Konsep Luas Permukaan Kubus dan Balok - Huswatun Hasanah (Indonesian Journal of Learning Education and Counseling, 2021)
The purpose of this study is to develop the didactical design concerning on the cube and cuboid surface concept. This study use Didactical Design Research measure in which it consists of three phases: (1) analysis of the didactic situation before learning that the form of design didactic hypothetical, (2) metapedadidactic analysis, and (3) retrospective analysis linked the results of analysis didactic situation hypothetical analysis and metapedadidactic analysis. This study has 96 secondary school’s students in the Cilegon city as research subjects. All datas were documented by using camera recording, interviews, and tests. The datas were analyzed qualitatively to determine the learning obstacle then researcher also compiled didactic design incorporating didactic pedagogical anticipation based on identified learning obstacles. Furthermore, the didactic design is implemented and analyzed the results of its implementation as a final product. The results obtained are a didactic concept design model surface area of cube and cuboid.